Citra Anak yang Baik pada Tokoh Utama Buku Cerita Bergambar Seri Nona Karya Dian Novitasari - Suprihatiningsih, Rizka; Formen, Ali; Setiawan, Deni (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Storybooks have an important role in building children's character. Through story books, children observe how the characters in them are, especially the main character. Previous studies focused a lot on character. This research aims to describe good children in the main character of the Nona Series picture book by Dian Novitasari which consists of 6 books. These books are Halo, Aku Nona, Ayo Bantu Ibu dan Ayah, Saatnya Bermain, Tersesat di Pasar, Hiih, Nona Takut! and Serunya Naik Angkutan Umum. The research employs a descriptive qualitative method. Data collection techniques utilize document analysis. The results of the study indicate that there are 16 good child images in the book. These images include being cheerful, independent, brave, helpful, tidy, exploratory, respectful of others, honoring parents, obedient, and socialize, likes animals, likes traditional games, brave, admits mistakes and apologizes and has initiative. This research can be used as a reference for educators and writers to create inspirational texts and images for young children.